Oscillation Between Resist and to Not? Users’ Folk Theories and Resistance to Algorithmic Curation on Douyin - Hui Lin (Social Media + Society)
An increasing number of users are aware of algorithmically driven content curation. Yet, while numerous studies have examined how people understand algorithmic power, there are insufficient numbers of studies about how people respond to and resist algorithmic curation in different sociocultural contexts. This article adopts a walk-through method and a diary-interview approach with 31 participants to investigate user resistance to algorithmic curation in different sociocultural circumstances. Drawing on the theoretical framework of folk theories and user resistance to algorithms, this study reveals a paradox in users’ algorithmic awareness and resistance behaviors: although respondents said they expressed annoyance with algorithmic simplification, commercial exploitation, and political agenda-setting, they often behaved in ways that contradict those claims with oscillated resistance to algorithmic curation. This study found that this paradox of resistance not only reflects users’ efforts to reconcile sociocultural needs with digital irritations caused by algorithmic mismatches but also arises from a sense of digital resignation in response to the platform’s strict regulations and censorship. Thus, this article argues that although people espouse folk theories as resources to resist algorithmic curation in different sociocultural contexts, most of their resistance behaviors remain constrained within the dominant use of technological affordances, which largely functions as a process of continuous negotiation rather than a subversive force capable of disrupting the ideological power relations embedded in algorithm-driven platforms.